Three-Day Combination Treatment for Vulvovaginal Candidosis with 200 mg Clotrimazol Vaginal Suppositories and Clotrimazol Cream for the Vulva is Significantly Better than Treatment with Vaginal Suppositories Alone – an Earlier, Multi-Centre, Placebo-Controlled Double Blind Study - Mendling, W.; Schlegelmilch, R. (Geburtshilfe und Frauenheilkunde, 2014)
Problem: According to the guidelines, acute vulvovaginal candidosis (VVC) may be treated vaginally, through a combination of vaginal treatment and cream for the vulva or orally. However, there is a lack of investigations into whether combined treatment for the vagina and vulva achieves better results than vaginal treatment alone. Method: In 1999, 160 patients with vulvovaginal candidosis from ten German gynaecological practices were included in a study and treated on a randomised basis with three 200 mg clotrimazol vaginal suppositories = clotrimazol 2 % cream (verum n = 79) or + placebo (active-ingredient-free cream base n = 79). The examinations took place before treatment (T1), six to eight days following the end of treatment (T2) and approximately four weeks following the end of treatment (T3). In addition to demographic data, the clinical findings of each investigation were documented in a standardised way and a native preparation and a fungal culture were taken. The doctor and patient evaluated the healing process and tolerance. The main efficacy variables were the pre/post difference scores for extravaginal redness. Results: On T1, there was no difference between the two groups. By T2, there was a significant difference in the extent of extravaginal redness between the verum and the placebo groups (p = 0.0002), as well as in the subgroup of the per-protocol analysis (verum 64, placebo 70 patients, p = 0.0015). Genital itching or burning had entirely disappeared in 51 % and 56 % of patients respectively in the verum group and in only 30 % and 45 % of patients in the placebo group on T2 (p = 0.0181). There was no difference in intravaginal redness on T1 and T2 in either group. The overall assessment by the doctor went accordingly (p = 0.0004). On T1, the extravaginal fungal culture was positive in 75 women in the verum group and in 76 women in the placebo group. On T2, however, this was positive in 51.9 % (verum) and 73.1 % (placebo) of cases, and a positive culture was evinced in the vagina in 6 vs. 8 women (7.5 vs. 10.1 %, p = 0.3802). The local tolerance in both groups was 70 % very good, and 29 vs. 27 % good. After four weeks (T3), 16 out of 23 patients in the verum group and only 8 out of 21 in the placebo group had negative extravaginal fungal cultures. Discussion: There is a lack of studies into the issue of whether vaginal treatment or combined vulvovaginal treatment of acute VVC would be more advantageous. However, there are two studies that support the significant results of this paper that when it comes to acute VVC, the combination of three 200 mg clotrimazol vaginal suppositories with clotrimazol cream 2 % is better than with vaginal suppositories alone.
Keywords: vaginal candidosis; clotrimazol vaginal suppositories; clotrimazol cream; combination treatment